(untitled) (CIPEEX, 2025)
Abstract: According to Rizzatto Nunes[1], the Brazilian Consumer Defense Code (CDC) (Law No. 8,078/1990) holds significant importance in ensuring legal protection for consumers in Brazil. This is because it acknowledges the consumer’s vulnerability in the face of the supplier’s economic power. In order to secure balance in consumer contractual relations, the CDC established fundamental guidelines for identifying abusive clauses, whose nullity must be recognized under Article 51.